The President's Kill List: Assassination in US foreign policy since 1945 - Luca Trenta (Edinburgh University Press, 2024)
From Fidel Castro to Qassem Soleimani, the US government has been involved in an array of assassinations and assassination attempts against foreign leaders and officials. The President’s Kill List reveals how the US government has relied on a variety of methods, from the use of poison to the delivery of sniper rifles, and from employing hitmen to simply laying the groundwork for local actors to do the deed themselves. It shows not only how policymakers decided on assassination but also the level of Presidential control over these decisions. Tracing the history of the US government’s approach to assassination, the book analyses the evolution of assassination policies and, for the first time, reveals how successive administrations - through private justifications and public legitimations – ensured assassination remained an available tool.